STRATEGI MENINGKATKAN SKILL KOMPETENSI PRESTASI BELAJAR PEWARNAAN RAMBUT PADA MAHASISWA TATA RIAS AKS-AKK YOGYAKARTA - Harwiyati, Enny (Jurnal Socia Akademika, 2024)
This research aims to improve hair coloring students' hair coloring learning achievement competency skills and the strategies used with the lecture, question and answer demonstration learning method, practical assignments. This type of research is quantitative research with a descriptive approach, data collection using objective tests, action tests to obtain data on hair coloring competency scores, documentation. The subjects in this research were AKS AKK cosmetology students in semesters II and IV. The research object was strategies for improving competency skills in the hair coloring course. The results of the research show that the average objective test result achieved by students is 78%, so the assessment is in the medium category and requires in-depth study of the material. In terms of hair coloring or hair coloring competency skill scores, students were able to reach an average score of 84.167, so this score is in the high category. The evaluation process is an action to determine the value of something and measurement is an action to determine area or quantity.